Online workshop on differential equations and function spaces, dedicated to the 80-th anniversary of D.Sc., Professor Mikhail L’Vovich Goldman - Burenkov, Viktor (Eurasian Mathematical Journal, 2025)
Online workshop on differential equations and function spaces, dedicated to the 80-th anniversary of D.Sc., Professor Mikhail L’Vovich Goldman